2020
DOI: 10.3390/ma13245588
|View full text |Cite
|
Sign up to set email alerts
|

Tooth-Colored CAD/CAM Materials for Application in 3-Unit Fixed Dental Prostheses in the Molar Area: An Illustrated Clinical Comparison

Abstract: The aim of this study was to compare the clinical properties of tooth-colored computer-aided design/computer-aided manufacturing (CAD/CAM) materials for the fabrication of a 3-unit fixed dental prostheses (FDPs) in the same clinical scenario. A 53-year-old female patient was supplied with a 3-unit FDP to replace a second premolar in the upper jaw. Restorations were fabricated from 3 mol%, 4 mol%, and 5 mol% yttrium oxide zirconia, zirconia with translucency gradient, indirect composite resin, polyetheretherket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
1
29
0
4
Order By: Relevance
“…The authors observed that three-unit FDPs manufactured from prepressed PEEK presented greater deformation and required higher loads (2354 N) to fracture when compared to the pressed ones in granular form (1738 N). Some studies report that PEEK is considered a suitable material for restorations in load-bearing occlusal areas [46][47][48][49][50]. However, due to the material elastic modulus, PEEK can be comparable with a temporary material [50].…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that three-unit FDPs manufactured from prepressed PEEK presented greater deformation and required higher loads (2354 N) to fracture when compared to the pressed ones in granular form (1738 N). Some studies report that PEEK is considered a suitable material for restorations in load-bearing occlusal areas [46][47][48][49][50]. However, due to the material elastic modulus, PEEK can be comparable with a temporary material [50].…”
Section: Discussionmentioning
confidence: 99%
“…Although the weight of the prosthesis does not represent a problem per se [18] regarding this last indication, a reduction in the prosthesis volume into the palatal defect by an implant-retained obturator and its higher stability can be considered a gain in the patient's quality of life [19]. Nevertheless, PEEK infrastructures should be veneered by lithium disilicate, veneering resins for laboratory use or polymethylmethacrylate to achieve desirable aesthetic requirements [20]. The bond strength between the veneering material and PEEK infrastructure must be strong enough to resist the adverse buccal environment which is subject to cyclic loading, different temperatures, and moisture [21].…”
Section: Introductionmentioning
confidence: 99%
“…Polyetheretherketone (PEEK), a high-performance polymeric material successfully utilized in traditional industrial fields, has been gradually introduced into dentistry and applied as a framework material of complete dentures, removable partial dentures, and implant-supported prostheses [1][2][3]. Compared with existing dental materials, PEEK shows better mechanical properties of flexural strength and fracture resistance [4,5]. Most reported PEEK prostheses were fabricated with the CAD/CAM milling technique, while the cost of excess material and time remain to be solved in the future [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with existing dental materials, PEEK shows better mechanical properties of flexural strength and fracture resistance [4,5]. Most reported PEEK prostheses were fabricated with the CAD/CAM milling technique, while the cost of excess material and time remain to be solved in the future [5][6][7]. Additive manufacturing, also named 3D printing, offers a remarkable utilization rate of the material and good shape ability, which has attracted the focus of researchers [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation